Demokrasi: Pergumulan Melawan Sang Demagog Refleksi Atas Pemikiran Plato, Aristoteles dan Hannah Arendt - Mikhael Dua (Respons: Jurnal Etika Sosial, 2009)
Abstract: As far as it develops, democracy has been practiced in many forms of civil states as the only way to reduce many forms of domination. The course of political history, however, shows that democracys is not the ideal form of the states, especially because it cannot be purified from the phenomena of the demagogues. The turn from democracy to tyranny can be explained from this point of view: democracy is the source of the demagogues. This paper will deal with the question of the relationship between democracy and the demagogues. By following Plato, Aristotle and Hannah Arendt who concern with the question of the essence of the politics, the paper brings forth the idea that the constitution of democracy should be developed into the constitution of the freedom of the people. In such a way, politics can be identified with the human togetherness.Kata Kunci: Demokrasi, demagog, kebebasan, konstitusionalisme, filsafat Yunani